Koncepcja wielopoziomowych systemów informatycznych zarządzania - Dziembek, Damian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The dynamic development of information and communication technology, the necessity for improvement of processes as well as environment change influence implementations of varied types of management information systems. Depending on specific decisions made on different levels of management the suitable information systems are created. The paper presents an idea of multi-level management information systems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 30-49